THE USE OF Q-PREPARATION FOR AMPLITUDE FILTERING OF DISCRETED IMAGE - Timchenko, Leonid; Kokriatskaia, Natalia; Rozvodiuk, Mykhailo; Tverdomed, Volodymyr; Kutaev, Yuri; Smailova, Saule; Plisenko, Vladyslav; Semenova, Liudmyla; Zhuk, Dmytro (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The article was aimed at improving the amplitude filtering process of the sampled image through the use of generalized Q-preparation. The existing correlation algorithms for image preprocessing were analyzed and their advantages and disadvantages were identified. The process of amplitude filtering and the main methods of preprocessing with such filtering were considered. A method of amplitude filtering of images based on the generalized Q-transformation with the use of sum-difference preprocessing of images has been developed. The efficiency of this method was analyzed, and a variant of the scheme for the corresponding preprocessing of images was proposed. The efficiency of the method was confirmed by computer simulation.